High impedance grounding fault location method for power cables based on reflection coefficient spectrum - Shurong Li; Borui Gu; Xiaoguang Zhu; Han Li; Junbo Deng; Guanjun Zhang (Energy Reports, 2023)
When a high impedance grounding fault occurs in the power cables, the current at the fault point is extremely low and the fault characteristics are too weak to be detected by the reflectometry. Interfered by the multiple reflections, the fault is hard to be located in the field. In order to solve the problem of conventional frequency domain reflectometry, a high impedance grounding fault location method for 10 kV distribution cables is proposed in this paper, which is based on the reflection coefficient spectrum. Firstly, the equivalent model of cable distributed parameters is established, and the reflection coefficient spectrum at the cable head is derived. Then, according to the theorem of integral transformation and generalized orthogonality, the diagnostic function is built in the spatial domain. Besides, the Kaiser window is introduced to improve the location sensitivity. Finally, the feasibility of the method is verified by simulated and experimental results. It is shown that this method can effectively eliminate the impact of multiple reflections, and precisely locate the single- and multi-point grounding faults. The fault location error is within 0.2%.